Effects of Calcium Salt of Palm Fatty Acid Distillate on the Growth Rumen Parameters, and Meat Quality of Sheep - Hassan Alwaheidi, Imad Nemer (2005)
The effects of dietary Ca-salt of palm fatty acid distillate (CSPFAD) as an energy supplement on sheep performance, carcass characteristics and meat quality were examined. Eighteen Santa Ines lambs weighing 16.6&1.4 kg were randomly allocated to three dietary treatments with six animals for each group. The lambs were fed a based diet containing palm kernel cake plus oil palm fi-ond (PKC+OPF) supplemented with either 0% (diet l), 2.5% (diet 2) and 5% (diet 3) calcium salt of palm fatty acid (CSPFAD). The feed intake, body weight and feed conversion ratio were recorded every two weeks for a period of 4 months. At the end of the experiment, 9 lambs (3 lambs from each dietary treatment) were randomly selected and slaughtered to examine carcass characteristics. Longissirnus dorsi (LD) muscle were sampled and examined for cooking loss and objective tenderness by Warner- Bratzler shear force analysis. In the second experiment three adult male sheep (51 * 2.12 kg body weight) fitted with ruminal cannulas were used, 3 x 3 Latin square design to determine the degradability of dry matter and protein at 6, 12,24,36 and 48 hr incubation time. The pH, ammonia nitrogen (NH3-N) and volatile fatty acid (VFA) of the rumen fluid were measured at 0, 2 and 4hr post-feeding and stored at -20C0 until analysis. The result shows there were no significant difference (P>0.05) in feed intake and body weight changes of the lambs among the dietary treatments. pH, total VFA, molar proportions of acetic acid, and acetic : propionic ratio of rumen fluid were not affected by dietary treatment. However, there was significant difference (P<0.05) in propionic acid molar proportion between the dietary treatment with the highest and lowest indicated in the 5% (diet 3) and control (diet I), respectively. Further more, the pH of meat, dressing percentage, and carcasses composition are similar (P>0.05) among the dietary treatments. However, cooking loss of meat increased (P<0.05) as the levels of CSPFAD was increased in the diet. Significant different (P<0.05) in shear force were observed between diets with highest and lowest indicated by the control and 5% dietary treatment respectively. It can be concluded that the CSPFAD can be used up to 5% as an energy source in a diet without any adverse effects on rumen fermentation. It can also enhanced meat quality such as tenderness.